Constraints on (2060) Chiron’s size, shape, and surrounding material from the November 2018 and September 2019 stellar occultations - Braga-Ribas, Felipe; Pereira, C. L.; Sicardy, B.; Ortiz, J. L.; Desmars, J.; Sickafoose, A.; Emilio, M.; Morgado, B.; Margoti, G.; Rommel, F. L.; Camargo, J. I. B.; Assafin, M.; et al. (Astronomy and astrophysics, 2023)
After the discovery of rings around the largest known Centaur object, (10199) Chariklo, we carried out observation campaigns of stellar occultations produced by the second-largest known Centaur object, (2060) Chiron, to better characterize its physical properties and presence of material on its surroundings. We aim to provide constraints on (2060) Chiron’s shape for the first time using stellar occultations. We investigate the detectability of material previously observed in its vicinity using the 2018 occultation data obtained from South Africa Astronomical Observatory (SAAO).